Flood Sedimentology for Future Floods Mitigation in North Luwu, Sulawesi, Indonesia - Adi Maulana; Miswar Tumpu; Indah Putri Indriani; Iswandi Utama (Civil Engineering Journal, 2023)
A sedimentological study after the flash floods that hit North Luwu on July 13, 2020, has been carried out on three affected rivers, namely the Masamba River, the Radda River, and the Binuang River. The study aims to determine the sedimentological impact of the 2020 flash flood disaster, including sedimentation rate, annual bedload sediment volume, and total sediments, which will be used as a reference for future mitigation consideration. The study is based on fieldwork for data collection and laboratory analysis. The results of field measurements and laboratory analysis are then processed by calculating the sedimentation rate at the annual discharge, the bedload sediment volume, and the total estimated sediment accumulated by the flash flood. Sedimentation rate analysis was performed using the Ackers-White formula, and flood delineation was processed using HEC-RAS software. The climatological data from the climatology station at Andi Djemma Airport were used to calculate the river discharge. It is estimated that the volume of bedload sediment in the Binuang River is 16,194,168 m3/year, that of the Masamba River is 7,852,061 m3/year, and that of the Radda River is 4,003,011 m3/year. The volume of sediment brought by flash flood sedimentation in the Radda River is 9,141,608.39 m3, while that in the Masamba River is 55,131,761.29 m3, and that in the Binuang River is 136,838,603.61 m3. The total estimated sedimentation generated by the flash flood on the three rivers on July 13, 2020, is 222,476,966 m3. Based on the study, zonation for vulnerability levels is designed for a future mitigation scheme. The zonation can be classified into three zones: 1) the highly affected zone; 2) the moderately affected zone; and 3) the least affected zone, with special purposes in each zone. It is strongly recommended that future disaster settlement and infrastructure reconstruction policies be based on this zone to reduce disaster risk. Doi: 10.28991/CEJ-2023-09-04-011 Full Text: PDF